Undersökningar av Paracastextilier. Dokumentation av gästkollegeprojekt - Hacke, Marei; Javér, Anna; Thuresson, Kaj (Swedish National Heritage Board, 2018)
Summary of data and analyses reports that form the background to the publication:

Javér, A., M. Hacke, C. Thays Delgado, and K.
Thuresson. 2017. Paracas textiles – Colour and
condition. Investigation of the mordants and state
of degradation of the Paracas textile collections
in Peru and Sweden. In ICOM-CC 18th Triennial
Conference Preprints, Copenhagen, 4–8 September
2017, ed. J. Bridgland, art. 1804. Paris: International
Council of Museums.
Keywords: History and Archaeology; Historia och arkeologi